F-MARC: promoting the prevention and management of sudden cardiac arrest in football - Kramer, E. B.; Dvorak, J.; Schmied, C.; Meyer, T. (British Journal of Sports Medicine, 2015)
Sudden cardiac death is the most common cause of unnatural death in football. To prevent and urgently manage sudden cardiac arrest on the football field-of-play, F-MARC (FIFA Medical and Research Centre) has been fully committed to a programme of research, education, standardisation and practical implementation. This strategy has detected football players at medical risk during mandatory precompetition medical assessments. Additionally, FIFA has (1) sponsored internationally accepted guidelines for the interpretation of an athlete's ECG, (2) developed field-of-play-specific protocols for the recognition, response, resuscitation and removal of a football player having sudden cardiac arrest and (3) introduced and distributed the FIFA medical emergency bag which has already resulted in the successful resuscitation of a football player who had a sudden cardiac arrest on the field-of-play. Recently FIFA, in association with the Institute of Sports and Preventive Medicine in Saarbrücken, Germany, established a worldwide Sudden Death Registry with a view to documenting fatal events on the football field-of-play. These activities by F-MARC are testimony to FIFA's continued commitment to minimising sudden cardiac arrest while playing football.